Case Report On Goblet Cell Adenocarcinoma Of The Appendix: A Rarity - Manikandan, Vinisha; N, Sriram.; Dheenadhayalan, M.; Karthickeyan, K.; Shanmugasundaram, P.; Sri, M.K.Sundar (Journal of Neonatal Surgery, 2025)
The rare appendix tumour known as the goblet cell carcinoid (GCC) is distinct from adenocarcinoma and other carcinoid tumours. The most typical symptoms are appendicitis, abdominal distention, and chronic abdominal pain. In this view, we present a case of a 41-year- old male patient who came with a complaint of right lower abdominal pain. Ultrasound abdomen revealed acute appendicitis. A laparoscopic appendicectomy was performed. Histopathological examination reported an appendix showing carcinomatous changes, goblet cell adenocarcinoma low grade. The patient agreed to proceed with a right hemicolectomy, 2- 4 weeks after his appendectomy. Our goal was to increase public awareness of this rare condition and also emphasize how challenging it is to diagnose correctly.